2013
DOI: 10.7314/apjcp.2013.14.7.4161
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Screening Between Preoperative and Postoperative Patients in Pancreatic Cancer

Abstract: Objective: To investigate discriminating protein patterns and potential biomarkers in serum samples between pre/postoperative pancreatic cancer patients and healthy controls. Methods: 23 serum samples from PC patients (12 preoperative and 11 postoperative) and 76 from healthy controls were analyzed using matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-TOF MS) technique combined with magnetic beads-based weak cation-exchange chromatography (MB-WCX). ClinProTools software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that Sn‐based alloying, including the addition of oxophobic elemental species such as Pb to Sn, improves the electrocatalytic activity of the electrodes 122. Oxidation treatment of Sn‐based alloys, such as Sn‐Pb‐Sb, has been found to largely improve the Faradaic efficiency of formate production without a reduction in the current density.…”
Section: Tin (Sn)mentioning
confidence: 99%
“…It has been demonstrated that Sn‐based alloying, including the addition of oxophobic elemental species such as Pb to Sn, improves the electrocatalytic activity of the electrodes 122. Oxidation treatment of Sn‐based alloys, such as Sn‐Pb‐Sb, has been found to largely improve the Faradaic efficiency of formate production without a reduction in the current density.…”
Section: Tin (Sn)mentioning
confidence: 99%
“…Due to its low sample volume requirements and excellent detection limits, MALDI MS is able to provide relative levels of peptides from rodent brain tissue samples that have not been pooled across multiple animals and/or brain regions (Li and Sweedler 2008;Miura et al 2010;Uys et al 2010;Romanova et al 2013Romanova et al , 2014. Comparative MALDI MSbased screening of peptides, lipids, and metabolites is actively being explored as a potential method for a nearly universal high throughput, cost-effective, sensitive, and discriminative diagnostic tool for various cancers (Shin et al 2007;Qiu et al 2009;Shevchenko et al 2010;Li et al 2013) and other pathological conditions (Hachani et al 2011;Ollero et al 2011;Perez et al 2014;Rico Santana et al 2014), and even cognitive dysfunction .…”
mentioning
confidence: 99%